Raising Healthy Children: Frugal Shopping Tips for Families - Julie M. Martinez; Shari Bresin; Karla P. Shelnutt (EDIS)
In today's uncertain economic times, families are cutting their budgets wherever possible to make ends meet. This includes reducing the amount of money spent on food. Although a tighter food budget may make grocery shopping a challenge, learning how to stretch food dollars can help families afford enough healthy foods for the whole family to enjoy. This publication will discuss ways to plan ahead and strategies to help stretch your food dollars. Written by Julie M. Martinez, Shari Bresin, and Karla P. Shelnutt, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised December 2020.